The Effect Of Motor Vehicle Tax Services On Taxpayer Satisfaction In The Samsat Of Bengkulu City - Atika Puspita Sari; Karona Cahya Susena; Rinto Noviantoro (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
The purpose of this study was to determine the effect of motor vehicle tax services on taxpayer satisfaction at the Bengkulu City SAMSAT office. This type of research is descriptive qualitative research, with data collection techniques used are observation and questionnaires. The data analysis technique used is descriptive quantitative analysis method.The results showed that from simple linear regression showed taxpayer satisfaction (Y) = 4.838 + 0.921X. The constant value of 4.838 means that if there is no tax service of zero (0), then the satisfaction of the taxpayer is 4.838. While the regression coefficient for tax services is 0.921, meaning that if tax services increase by 1%, then taxpayer satisfaction will also increase or increase by 5.759% (4.838 + 0.921).